Perceptions of the circular economy: insights from Twitter - Guzmán-Rivera, Alejandro; Ciechanowski, Kaśmir; Jemielniak, Dariusz (Journal of Management and Financial Sciences, 2025)
This study investigates the evolving discourse on the circular economy (CE) on Twitter from 2015 to 2022. Leveraging sentiment analysis and keyword frequency tracking, we analyzed 513,709 tweets containing the hashtag #CircularEconomy. The study identifies prominent keywords, including sustainability, recycling, and innovation, and tracks their frequency over the years. Notably, circular economy reveals an overall neutral sentiment, gradually shifting towards positivity. We observe dynamic patterns in the discussion of the 3Rs (Reduce, Reuse, and Recycle), indicating varying emphases over time. The VADER sentiment scores underscore a nuanced shift towards positive sentiment. The findings contribute to understanding the public’s engagement with CE concepts on social media and provide insights for further research and communication strategies.